Deep Infections After Pediatric Spinal Arthrodesis: Differences Exist with Idiopathic, Neuromuscular, or Genetic and Syndromic Cause of Deformity. (18th December 2019) - Sullivan, Brian T.; Abousamra, Oussama; Puvanesarajah, Varun; Jain, Amit; Hadad, Matthew J.; Milstone, Aaron M.; Sponseller, Paul D.
Abstract : Background: Little is known about the rates, timing, and causative microorganisms of deep surgical site infections after spinal arthrodesis in patients with genetic and syndromic scoliosis compared with patients with adolescent idiopathic scoliosis and kyphosis or patients with neuromuscular scoliosis. Methods: We reviewed data from 1, 353 patients who were <21 years of age and had undergone spinal arthrodesis for deformity correction by 1 surgeon from 2000 to 2015. Deformity causes were genetic, idiopathic, or neuromuscular. We identified patients who had undergone an unplanned surgical procedure for a deep surgical site infection that was early (⩽90 days after the procedure) or late (>90 days after the procedure). We compared deep surgical site infection rates, timing, and causative microorganisms by deformity cause. Results: Deep surgical site infections occurred in 65 patients (4.8%): 4.2% for patients with genetic and syndromic scoliosis, 2.7% for patients with adolescent idiopathic scoliosis and kyphosis, and 10.0% for patients with neuromuscular scoliosis. Of the deep surgical site infections, 26 (40%) occurred early and 39 (60%) occurred late. The median times to deep surgical site infection onset were 51 days (range, 7 days to 7 years) in patients with genetic and syndromic scoliosis, 827 days (range, 10 days to 12 years) in patients with adolescent idiopathic scoliosis and kyphosis, and 45 days (range, 13 days to 6 years) in patients with neuromuscular scoliosis. Seventy-six microorganisms (41 gram-positive and 35 gram-negative) were isolated from 47 children with positive cultures; the most common was coagulase-negative Staphylococcus (n = 13). The ratio of gram-positive to gram-negative microorganisms was highest in patients with adolescent idiopathic scoliosis and kyphosis (4:1) and lowest in patients with genetic and syndromic scoliosis (0.5:1). In genetic and syndromic scoliosis, both early and late deep surgical site infections were more frequently caused by gram-negative bacteria. In neuromuscular scoliosis, early deep surgical site infections were more frequently caused by gram-negative bacteria, and late deep surgical site infections were more frequently caused by gram-positive bacteria. In adolescent idiopathic scoliosis and kyphosis, both early and late deep surgical site infections were more commonly caused by gram-positive bacteria. Methicillin-resistant Staphylococcus aureus was identified in 2 late deep surgical site infections in patients with neuromuscular scoliosis. Conclusions: Deep surgical site infections were more common in genetic and syndromic scoliosis than in adolescent idiopathic scoliosis and kyphosis, but less common than in neuromuscular scoliosis. Adolescent idiopathic scoliosis and kyphosis had the highest ratio of late to early deep surgical site infections. Patients with genetic and syndromic scoliosis had predominantly gram-negative microorganisms, particularly in early deep surgical site infections. Methicillin-resistant S. aureus infection was rare, occurring in only 2 patients with neuromuscular scoliosis. Gram-negative and gram-positive prophylactic antibiotics may be indicated for patients with genetic and syndromic scoliosis after spinal arthrodesis. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.